INTERNAL INNOVATION OF TABA IN NORTHERN MALUKU HISTORICAL LINGUISTICS PERSPECTIVE - Burhanuddin Burhanuddin (Humanus: Jurnal Ilmiah Ilmu-ilmu Humaniora, 2017)
The paper explains the internal phonological and lexical innovations in Taba language in North Maluku from historical linguistics perspective. 200 and 1000 basic and cultural vocabulary, respectively, have been collected using note-taking and recorded interviews in Taba language and other related languages, including Buli, Maba, Sawai, Gebe, and Gane. Data were analysed using horizontal approach, employing intralingual comparative-linking method. The analysis reveals that Taba language has nine phonological propensities which are unidentified in other languages in North Maluku. These include (1) realization of /s/ in the final position, preceded by dental consonants /d, t/; (2) omission, as opposed to appearance in other languages, of the first syllable; (3) realization of vowel /o/ in penultima sylable (otherwise i-o sequence in different syllables); 4) realization of consonant /h/ in ultima and penultima sylables; 5) realization of consonant /c/in the initial potition; 6) regular realization of vowel /a/ in the initial penultima syllable; 7) omission of the first syllable, followed by an addition of either a phoneme or syllable in the final position; 8) realization of /k/ in the final position; and 9) realization of /h/ in the central position. Meanwhile, the internal lexical innovation (the difference with the other five languages of South Halmahera is horizontal) can be observed in as such words that refer to awan ‘cloud’, baik ‘good’, belok ‘to turn’, gigit ‘to bite’, dekat ‘near’, ikat ‘bundle’, jahit ‘stitch’, jarum ‘needle’ and jika‘if’.Key words: internal innovations, historical linguistics, phonological innovations, lexical innovations.INOVASI INTERNAL BAHASA TABA DI MALUKU UTARA: PERSPEKTIF LINGUISTIK HISTORISAbstrakTulisan ini bertujuan menjelaskan inovasi internal aspek fonologi dan leksikal bahasa Taba di Maluku Utara dari perspektif studi linguistik historis. Data berupa 200 kosa kata dasar dan 1000 kosa kata budaya telah dikumpulkan dengan metode wawancara/cakap teknik catat dan rekam dalam bahasa Taba, dan lima bahasa lain yang sekerabatnya dengannya, yaitu Buli, Maba, Sawai, Gebe, dan Gane. Lalu, data dianalisis menggunakan pendekatan horizontal metode padan intralingual, teknik hubung-banding. Dalam bahasa Taba setidak-tidaknya memiliki sembilan kecenderungan fonologis yang tidak dimiliki oleh bahasa Halmahera Selatan lainnya. Yaitu, (1) merealisasikan bunyi /s/ pada posisi akhir yang diawali konsonan dental /d, t/; (2) mengalami penghilangan suku awal, sedangkan bahasa lain sebaliknya (muncul); (3) merealisasikan vokal /o/ (perendahan vokal) pada silabe penultima (atau pada urutan i-o pada silabe berbeda); (4) merealisasikan konsonan /h/ baik pada silabe penultima maupun ultima; (5) merealisasikan konsonan /c/ pada posisi awal; (6) merealisasikan vokal /a/ secara teratur pada silabe awal penultima; (7) terjadi penghilangan suku awal diikuti oleh penambahan fonem atau silabe pada posisi akhir; (8) merealisasikan /k/ pada posisi akhir; serta (9) merealisasikan bunyi /h/ pada posisi tengah. Adapun inovasi leksikal (perbedaannya dengan lima bahasa Halmahea Selatan lainnya secara horizontal) di antaranya dapat ditemukan pada kata yang bermakna ‘awan’, ‘baik’, ‘belok’, ‘gigit’, ‘dekat’, ‘ikat’, ‘jahit’, ‘jarum’, ‘jika, kalau’, dan sebagainya.Kata kunci: inovasi internal, linguistik historis, inovasi fonologi, dan inovasi leksikal.